Building a Respect Learning Environment to Reduce Bullying by Teachers - Musthofa, Achmad; Muhammad, Devy Habibi (UAS PRESS, 2024)
This research aims to investigate how teachers can effectively address and reduce bullying in schools and the strategies they use to create a respectful and supportive learning environment. At Muhammadiyah Junior High School in Pasuruan Regency, bullying manifests in several ways, such as upperclassmen intimidating younger students, inappropriate social exclusion, and coercive actions involving personal belongings that cause distress to victims. The study employs a qualitative, descriptive case study approach, focusing on detailed participant experiences without extensive theoretical analysis. Data collection includes interviews and observations, with an emphasis on ensuring the findings' validity and reliability. The findings suggest that schools should implement weekend character education programs led by Islamic Education teachers, with sessions concluded by Guidance and Counseling teachers. These programs encourage students to adopt positive character traits in their daily lives. Muhammadiyah Junior High School in Pasuruan Regency is committed to enforcing strong anti-bullying policies and fostering a collective approach to combat all forms of bullying, aiming to establish a safe and respectful learning environment for every student.